Zeolite Amended Coastal Sandy Soils Improve Nitrogen Use Efficiency in Maize Vegetative Growth - Fahmi Budiayanto (Athallah Publishing globalindo, 2025)
Coastal sandy soils are characterized by low nutrient retention and high nitrogen (N) losses, which limit crop productivity and reduce nitrogen use efficiency (NUE). This study aimed to evaluate the effect of zeolite amendment on nitrogen use efficiency and vegetative growth of maize cultivated in coastal sandy soils. A controlled field experiment was conducted using a randomized block design with different rates of zeolite application combined with nitrogen fertilizer. Parameters observed included plant height, leaf number, leaf area, chlorophyll content, biomass accumulation, and nitrogen uptake during the vegetative growth stage. The results showed that zeolite-amended soils significantly improved soil cation exchange capacity and reduced nitrogen leaching, leading to higher nitrogen availability for plant uptake. Consequently, maize grown in zeolite-treated plots exhibited significantly enhanced vegetative growth and higher NUE compared to the control without zeolite. The highest zeolite application rate resulted in optimal nitrogen uptake and biomass production. These findings indicate that zeolite amendment is an effective soil management strategy to enhance nitrogen use efficiency and improve maize vegetative growth in coastal sandy soils, contributing to more sustainable and efficient fertilizer use in coastal agricultural systems.